2008
DOI: 10.1128/iai.01497-07
|View full text |Cite
|
Sign up to set email alerts
|

Combined Inactivation of the Candida albicans GPR1 and TPS2 Genes Results in Avirulence in a Mouse Model for Systemic Infection

Abstract: Inhibition of the biosynthesis of trehalose, a well-known stress protectant in pathogens, is an interesting approach for antifungal or antibacterial therapy. Deletion of TPS2, encoding trehalose-6-phosphate (T6P) phosphatase, results in strongly reduced virulence of Candida albicans due to accumulation of T6P instead of trehalose in response to stress. To further aggravate the deregulation in the pathogen, we have additionally deleted the GPR1 gene, encoding the nutrient receptor that activates the cyclic AMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 40 publications
1
27
1
Order By: Relevance
“…Mice were infected via the lateral caudal vein with 0.1 ml of a C. albicans suspension containing 1 ϫ 10 6 cells (17). Animal survival was evaluated daily (18).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were infected via the lateral caudal vein with 0.1 ml of a C. albicans suspension containing 1 ϫ 10 6 cells (17). Animal survival was evaluated daily (18).…”
Section: Methodsmentioning
confidence: 99%
“…Biochemical studies revealed that Gpr1 and Gpa2 are required for the glucose-dependent increase in intracellular cAMP levels (386), and they are important for amino-acid-induced morphogenesis in the presence of glucose (358). Although gpr1 and gpa2 homozygous deletion mutants are fully virulent in the mouse (386), the combined deletion of GPR1 and TPS2, encoding the trehalose-6-phosphate phosphatase, results in avirulence in a mouse model of infection (356). Ras1 is a guanine nucleotide binding protein which acts downstream of Mep2.…”
Section: Major Morphogenetic Signaling Cascadesmentioning
confidence: 99%
“…Active Growth in C. albicans-Previous findings have shown that absence of GPR1 in C. albicans leads to increased trehalose content as well as activity of the Tps1 enzyme, especially in heat shock conditions (30). We investigated the role of Gpr1 on trehalose content in C. albicans in conditions of 37°C, the physiological temperature that is not experienced as a stress in the pathogenic fungus.…”
Section: Gpr1 Is Required For Lowering Trehalose Content Duringmentioning
confidence: 99%
“…As gpr1⌬/gpr1⌬ cells accumulate trehalose even at 30°C while actively growing (data not shown and Ref. 30), we investigated whether geldanamycin was able to induce the filamentation phenotype in the mutant strain. Whereas extrusions of the cells were readily observed in wild type upon addition of geldanamycin at the noninducing temperature of 30°C, the gpr1⌬/gpr1⌬ mutant was partially defective in this response (Fig.…”
Section: Trehalose Restrains Cell Elongation By Release Of Hsp90mentioning
confidence: 99%
See 1 more Smart Citation